Media and Democratisation: Challenges for an Emerging Sub-field - Nael Jebril; Matthew Loveless; Vaclav Stetka (Medijske Studije, 2015)
This article seeks to compile an empirically-based understanding of the role of media in countries in transition. The study focuses on the processes of political socialization, behaviour and accountability, and gives examples from three regions: Central and Eastern Europe, Latin America, and the Middle East/North Africa region. We draw on some of the major works relevant to the study of mass media in these transitional contexts with the aim of discerning emergent theories available to the study of media and democratisation. While aware of the limitations posed by the nature and scope of the sample of the studies reviewed, we do identify and discuss some of the potentially key obstacles to theory-building and propose some alternative paths of enquiry.